FRI0465 Autologous Haematopoietic Stem Cell Transplantation for Takayasu's Arteritis: Report of 3 Cases. (10th June 2014) - Moraes, D.; Dias, J.; Stracieri, A.B.; Pieroni, F.; Cunha, R.; Malta, R.; Zombrilli, A.; Nilsen, L.; Leopoldo, V.; Simoes, B.; Oliveira, M.C.
Abstract : Background: Takayasu's arteritis is a rare autoimmune vasculitis that affects medium and large vessels, especially the aorta and its main branches. Autologous stem cell transplantation for autoimmune disease has been shown to be effective in some refractory cases. Objectives: Describe our experience with autologous hematopoietic stem cell transplantation (AHSCT) in Takayasu's arteritis. Methods: Three patients with refractory Takayasu's arteritis were treated with AHSCT. Hematopoietic stem cells were mobilized with 2g/m 2 cyclophosphamide plus G-CSF, and subsequently harvested by leukoapheresis and cryopreserved, nonmanipulated. Patients then received 200mg/kg IV cyclophosphamide and 4.5mg/kg rabbit anti-thymocyte globulin (ATG) over five consecutive days, followed by infusion of the cryopreserved cells. Results: The procedure was well tolerated by all patients. Side effects included fever, rash, nausea, vomiting and neutropenic fever. None of the patients presented severe side effects during or after AHSCT. One patient presented CMV reactivation after transplant and was preemptively treated, without clinical manifestations of disease.Case 1: 41 year-old female, with a history of dizziness, claudication of upper and lower limbs, non-palpable right radial pulse and transient visual impairment for over 13 years. Arteriography showed irregularity and stenosis of abdominal aorta, right and left iliac arteries, left subclavian and carotid arteries. She had been unsuccessfully treated with steroids, methotrexate, cyclophosphamide, chlorambucil and mycophenolate mofetil. On follow-up of 127 months after AHSCT, she presented clinical and laboratory remission. Case 2: 30 year-old female, with intermittent visual deficits, upper limb claudication, subclavian steal syndrome and 3 episodes of transient ischemic strokes. Previous treatments included steroids, azathioprine, cyclophosphamide and mycophenolate mofetil, besides a stent placed in the right carotid artery. On 43 months follow-up, she remained symptomatic with high levels of acute phase reactants, indicating refractoriness to AHSCT. After transplant, she also failed etanercept injections, but disease activity was further controlled with tocilizumab. Case 3: 39 year-old male with intestinal claudication, renovascular hypertension, upper limb claudication and dizziness. Magnetic angioresonance (NMR) images evidenced right renal and mesenteric artery stenosis, and bilateral critical narrowing of carotid, subclavian, brachial and axilary arteries, and irregularities along the aorta. On 15 months follow-up, there was clinical and laboratorial improvement. Patients 1 and 3 presented partial reversal of vessel stenosis detected by NMR images. Conclusions: Very few cases of vasculitides treated with AHSCT have been reported in the literature. To the best of our knowledge, this is the largest reported series of transplanted Takayasu's patients. Although response to transplant was not universal, beneficial effects were verified in two out of three patients, who remained in remission for long periods. References: Voltarelli JC et al. Haematopoietic stem cell transplantation for refractory Takayasu's arteritis. Rheumatology 2004, 43:1308-9. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5103